Armazenamento de murici (Byrsonima crassifolia (L.) Rich) em diferentes temperaturas com aplicação de biofilme - Mota, Valdeci Aparecido (2014)
The murici (Byrsonima crassifolia (L) Kunth) is a typical fruit of the cerrado region, found from December to March. His trade is restricted only in the native region can be consumed raw or in the form of juices, jellies, ice cream and liqueurs. Studies aimed to extend the postharvest life of fruits has been developed in order to reduce losses and prolong product shelf market. Thus, this experiment aimed to evaluate the storage of fruits murici treated biofilms and stored at different temperatures and evaluate its physical and chemical characteristics compared with a control group without treatment. With this experiment, we hope to contribute to the maintenance of fruit quality for longer life fresh and collaborate with conservation methods for fruit postharvest. The fruits were harvested in the municipality of Wormleysburg - EC. The fruits of murici initially were greeted at the Laboratory of Quality Control and Food Drying / Federal University of Ceará (UFC), selected, washed, sanitized with a solution of 1% sodium hypochlorite, dried and subsequently treated with coatings based cassava starch and propolis extract in different concentrations (2%, 4% and 6%) by 2 minutes immersion, and also the control group without treatment. After application of the coating and drying the fruit, they were stored under refrigeration (12±2 ºC) and room temperature (25±2 °C) and analyzed during 10 days of storage at intervals of 2 in 2 days. The analyzes carried out during the period of storage of fruits were: size and shape of fruit (cm), weight (g), color (L*, a*, b*, C* and Hue°), vitamin C (mg/100 g), pH, titratable acidity (%) organic acids) (TA), soluble solids (° Brix) (SS) ratio (SS/TA), humidity (%) and water activity (Aw) solids. All analyzes were performed in triplicate. The average results obtained in the experiment were subjected to analysis of variance by ANOVA and for the comparison of means, the Tukey test at 5% probability was used by Sisvar statistical program. For the results, it was observed that the applied treatments, propolis extract caused major injuries, accelerating the ripening and senescence of fruits thus making it unaffordable as conservation methods. As for the other treatments, chilled fruit along with the biofilm of cassava starch at 4%, maintained the fruits with the highest physical and chemical quality for a longer period. Therefore, despite the gain parameters similar to control group behavior, it is possible to observe that they had different averages as with vitamin C, which had the smallest loss for fruits treated with cassava starch. Thus, the use of conservation methods such as refrigeration and biofilms were effective in maintaining fruit quality, which provided them with more time for consumption.